Aplicação do algoritmo de otimização por colônia de formigas aos problemas de reconstrução de árvores filogenéticas e dobramento de proteínas - Perretto, Maurício (2005)
The human being has great esteem for the reasoning process developed during its evolution. One of the areas of the computation was developed with the initial objective to simulate human intelligence inside computational programs. This area is known as artificial intelligence. In the last decades artificial intelligence has been basing on the most diverse forms of organization that have standards. One of these methods is the ant colony optimization algorithm, presented in the beginning of nineties, and that achieved good results for some problems that had had implemented models. Molecular biology aims to analyze the molecular structures present in living creatures, amongst them the sequences of DNA, RNA and protein aminoacids. Due to great number of information being confronted in this analysis it is impracticable in terms of processing time a search in the whole space of possible solutions, what makes interesting the use of algorithms that cover the search space efficiently. One of the problems of molecular biology is phylogenetic trees reconstruction. It aims to relate hereditarily the several species through information present in its sequences. In that manner, it is possible to know which species are more closely related to one another and which are more distantly related.